PENERAPAN COOPERATIVE LEARNING TIPE STAD DALAM MENINGKATKAN MOTIVASI TAHFIDZ AL QUR’AN PADA SISWA SEKOLAH DASAR - Aulia Siti Afiyah; Sarah Saliha; Ikmala Dina Syarifa; Intan Widi Kusuma (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT Qur’anic memorization activities among elementary school students often take place in learning situations that position learners primarily as recipients of instruction, while opportunities to develop shared learning experiences remain limited. This condition is reflected in students’ hesitation when reciting their memorization, uneven participation during learning activities, and fluctuating levels of enthusiasm throughout the learning process. Within this context, Qur’anic memorization learning in a second-grade elementary classroom was examined through the implementation of the Student Teams Achievement Division (STAD) model to explore how learning motivation develops during the memorization process. This study employed a descriptive qualitative approach involving a Qur’anic memorization teacher and second-grade students as research participants. Understanding of the phenomenon was developed through direct classroom observations and the examination of documents related to memorization activities. Interactions established through talqin, group murojaah, peer listening sessions, and memorization recitations created a more participatory learning pattern compared to teacher-centered practices. Student engagement was reflected in their willingness to recite memorized verses, persistence in repeating memorization, readiness to assist peers, and active participation in group activities. The collaborative learning experiences that emerged suggest that motivation develops not merely from achieving memorization targets, but also through social support, self-confidence, and opportunities to take an active role in the learning process. Qur’anic memorization learning, therefore, can be understood not only as a means of strengthening memorization skills but also as a social learning experience that sustains student engagement over time. ABSTRAK Kegiatan menghafal Al-Qur’an pada siswa sekolah dasar sering kali berlangsung dalam situasi yang menempatkan siswa sebagai penerima arahan, sementara kesempatan untuk membangun pengalaman belajar bersama masih relatif terbatas. Kondisi tersebut tampak pada munculnya keraguan ketika menyetorkan hafalan, keterlibatan yang belum merata selama pembelajaran, serta antusiasme yang cenderung berfluktuasi. Dalam konteks tersebut, pembelajaran tahfidz Al-Qur’an di kelas II sekolah dasar diamati melalui penerapan model Student Teams Achievement Division (STAD) untuk memahami bagaimana motivasi berkembang selama proses belajar berlangsung. Kajian ini menggunakan pendekatan kualitatif deskriptif dengan melibatkan guru tahfidz dan siswa sebagai informan. Pemaknaan terhadap fenomena dilakukan melalui pengamatan langsung selama pembelajaran dan telaah dokumentasi yang berkaitan dengan aktivitas tahfidz. Interaksi yang terbentuk melalui talqin, murojaah kelompok, penyimakan hafalan, dan setoran hafalan menghadirkan pola belajar yang lebih partisipatif dibandingkan praktik yang berpusat pada guru. Keterlibatan siswa terlihat melalui keberanian menyetorkan hafalan, ketekunan melakukan pengulangan bacaan, kesediaan membantu teman, serta partisipasi aktif dalam aktivitas kelompok. Pengalaman belajar yang dibangun melalui kerja sama tersebut memperlihatkan bahwa motivasi tidak berkembang semata-mata karena target hafalan, melainkan melalui dukungan sosial, rasa percaya diri, dan kesempatan untuk mengambil peran dalam proses belajar. Pembelajaran tahfidz pada akhirnya tampak sebagai ruang yang tidak hanya menguatkan hafalan Al-Qur’an, tetapi juga membentuk pengalaman belajar sosial yang mendukung keterlibatan siswa secara berkelanjutan.